Implementation of The Toddler Family Development Program to Reduce Stunting Rates by The Lingga Regency Health Department: Case Study East Lingga Subdistrict, 2025 - Ahlam Najib; Nazaki Nazaki; Kustiawan Kustiawan (Anthroposia: Journal of Social and Human Development, 2026)
Stunting remains a public health issue that requires effective policy implementation to address its prevalence. One of the efforts undertaken by the Government of Lingga Regency to reduce stunting rates is through the Toddler Family Development Program (Bina Keluarga Balita-BKB). However, the implementation of the program continues to face various challenges, particularly in East Lingga District, which records the highest stunting rate in Lingga Regency. This study aims to analyze the implementation of the Toddler Family Development Program (BKB) by the Health Office, Population Control, and Family Planning Agency of Lingga Regency using George C. Edward III’s policy implementation theory, which consists of communication, resources, disposition, and bureaucratic structure. The study employed a qualitative approach with a descriptive method. Informants were selected through purposive sampling and included officials from the Health Office, Population Control and Family Planning Agency, family planning counselors, BKB cadres, and mothers of stunted toddlers. Data were collected through interviews, observations, and documentation and were analyzed using the Miles, Huberman, and Saldaña interactive analysis model. The findings indicate that the implementation of the BKB Program has generally been carried out effectively. The dimensions of communication, disposition, and bureaucratic structure have supported program implementation through coordination, implementers’ commitment, and a clear division of responsibilities. Nevertheless, the resource dimension remains a significant challenge, particularly the limited number of cadres, inadequate counseling assistance that has not yet reached all villages, and insufficient Posyandu facilities and infrastructure. Strengthening human resources and improving supporting facilities are therefore essential to optimize the implementation of the BKB Program in accelerating stunting reduction efforts.